KNOWLEDGE MANAGEMENT FOR CHANGE PROCESS ACADEMIC IN HIGH SCHOOL - Norma Fitria (IAI AGUS SALIM METRO LAMPUNG, 2022)
The quality of knowledge of each individual depends on the experience that each individual has. There are two factors that affect a person's knowledge, namely the diversity of experience and experience that is used as a source of knowledge. Diversity of experience can be generated through varied activities, not fixated on a routine activity so that it will produce creative thinking. These varied activities are usually facilitated by the organization or company, such as training, workshops, seminars or activities that are other employee learning interventions. Experience that is used as a source of knowledge can be formed by an individual's commitment to want to learn when he gets an experience that will form knowledge. The knowledge contained in this process is tacit knowledge that must be disseminated or transferred so that each individual can further add or expand his or her inner knowledge. Experience that is used as a source of knowledge can be done by interacting with colleagues about experiences, perspectives, reading books, trusted articles found on the internet, mass media and social media. Conceptualization can be realized in communication between individuals. In a good communication, each individual must convey or share his knowledge in an organized and systematic manner, conduct dialogue between individuals or discussions that run smoothly and well. Each individual must also have the freedom to express ideas, enthusiasm in expressing opinions or ideas,